Unilateral ureteral triplication with duplex kidney and megaureter - Bhattacharyya S; Basu K; Samanta N (Wolters Kluwer Medknow Publications, 2005)
We report a case of duplex kidney with Type-2 ureteral triplication, with one megaureter having stenosis at its lower end and dysplasia of the upper moiety of the kidney. The child presented with lump abdomen and recurrent attacks of urinary tract infection. The child underwent excision of the dysplastic part of the kidney and megaureter with an ureteroureterostomy connecting the normal caliber lower ureter (U3) draining in trigone with the mildly dilated middle ureter (U2) draining into the megaureter (U1) of the upper moiety. The patient is well 2 months postoperatively with no urinary infection and stable renal function.